2024
DOI: 10.3389/feduc.2024.1309642
|View full text |Cite
|
Sign up to set email alerts
|

Technostress in students and quality of online learning: role of instructor and university support

Farida Saleem,
Emna Chikhaoui,
Muhammad Imran Malik

Abstract: Online learning provides flexibility and convenience to students, however, it also presents various challenges, such as technostress. Technostress is the psychological discomfort or stress experienced by individuals due to the use of technology, particularly when they cannot cope with its demands. Students’ technostress levels can have a negative impact on their online learning experiences. Drawing from the Community of Inquiry (CoI) framework, the study investigates the moderating impact of instructor and uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
1
1
0
Order By: Relevance
“…Such emotional co-regulation among colleagues are more easily established based on mutual trust relationships. Students can benefit from teacher support and our study identified similar results as previous study in terms of lower levels of technostress while students perceived their teacher support ( Saleem et al, 2024 ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Such emotional co-regulation among colleagues are more easily established based on mutual trust relationships. Students can benefit from teacher support and our study identified similar results as previous study in terms of lower levels of technostress while students perceived their teacher support ( Saleem et al, 2024 ).…”
Section: Discussionsupporting
confidence: 88%
“…The relations between technostress and instructional process is not always straight forward as students are not alone in the educational context. Saleem et al (2024) showed that support from the teacher and from the university mitigate the negative impact of technostress on quality of online learning in students.…”
Section: Literature Reviewmentioning
confidence: 99%